Carbohydrate-Based Micro/Nanocapsules With Controlled External Surface for Medical Applications - Bielski, Roman; Witczak, Zbigniew J.; Newport, John F. L. (Frontiers in Chemistry, 2020)
Micro/nanocapsules would have many more applications if we were able to controllably populate their surface with various chemical moieties. The present paper introduces a novel variant of interfacial polymerization (IP) as a very robust method of manufacturing reservoir micro/nanocapsules equipped with several different functionalities on the capsules’ surface. We call the method – IPCESCO (Interfacial Polymerization for Capsules’ External Surface Control). As always in IP, the capsules’ forming reaction is between monomers dissolved in opposite phases (oil or water) and takes place at the interface. Each monomer carries two or more functionalities reacting with functional groups of the monomer dissolved in the other phase. IPCESCO requires that one or both monomers are additionally equipped with (protected) functional groups interfering neither with the payload nor with the polymer formation. These additional groups end up everywhere in the polymeric shell but most importantly they are present on the external surface of capsules. These “handles” allow for the introduction of various moieties onto the capsules’ surface. Since carbohydrate chemists developed a plurality of protecting and deprotecting methods for various functional groups such as aldehyde and hydroxyl, modified mono and oligosaccharides are particularly well suited to act as monomers in IPCESCO. The paper discusses possible monomers and their synthesis, the transformation of protected reactive groups on the external capsules’ surface into the desired functionalities, the control of the number of moieties on the surface and the capsules surface’s architecture. The most important application of the novel encapsulation technology is in drug delivery. Possible surface units facilitating capsules’ transport in the body, delivery to specific locations and mechanisms of capsules rupture are also addressed. Other applications of novel capsules include an ultra-sensitive quantitation and removal of pathogens, transport of nutrients in plants, detection of various antigens and other parameters in single cells, etc.